2005
DOI: 10.1186/1471-2105-6-233
|View full text |Cite
|
Sign up to set email alerts
|

GeneRank: Using search engine technology for the analysis of microarray experiments

Abstract: Background: Interpretation of simple microarray experiments is usually based on the fold-change of gene expression between a reference and a "treated" sample where the treatment can be of many types from drug exposure to genetic variation. Interpretation of the results usually combines lists of differentially expressed genes with previous knowledge about their biological function. Here we evaluate a method -based on the PageRank algorithm employed by the popular search engine Google -that tries to automate som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(132 citation statements)
references
References 17 publications
2
130
0
Order By: Relevance
“…PageRank centrality is based on the importance (specifically the PageRank centrality) of a node’s neighbors. A node with high PageRank centrality may not necessarily maintain many strong, functional connections (i.e., have high degree centrality) but maintains functional connections with neighboring nodes that are highly central to the network (Boldi et al, 2009; Morrison et al, 2005); it should be noted that similar centrality measures (e.g., eigenvector centrality, betweenness centrality) may also similarly examine this property but we chose PageRank centrality (vs. eigenvector centrality or betweenness centrality) because it has been shown to be more sensitive to age-related effects (Khazaee et al, 2016; Zuo et al, 2012). The use of these two graph metrics allowed us to examine the three previously described ways a module may become central to a network, which, again, may be through (a) maintaining strong functional connections (high degree centrality but low PageRank centrality), (b) becoming more reliant on highly central nodes in other modules (high PageRank centrality but low degree centrality), or (c) both (high degree centrality and PageRank centrality).…”
Section: 0 Introductionmentioning
confidence: 99%
“…PageRank centrality is based on the importance (specifically the PageRank centrality) of a node’s neighbors. A node with high PageRank centrality may not necessarily maintain many strong, functional connections (i.e., have high degree centrality) but maintains functional connections with neighboring nodes that are highly central to the network (Boldi et al, 2009; Morrison et al, 2005); it should be noted that similar centrality measures (e.g., eigenvector centrality, betweenness centrality) may also similarly examine this property but we chose PageRank centrality (vs. eigenvector centrality or betweenness centrality) because it has been shown to be more sensitive to age-related effects (Khazaee et al, 2016; Zuo et al, 2012). The use of these two graph metrics allowed us to examine the three previously described ways a module may become central to a network, which, again, may be through (a) maintaining strong functional connections (high degree centrality but low PageRank centrality), (b) becoming more reliant on highly central nodes in other modules (high PageRank centrality but low degree centrality), or (c) both (high degree centrality and PageRank centrality).…”
Section: 0 Introductionmentioning
confidence: 99%
“…NetBC uses the GeneRank algorithm 51 to assign weights to genes. Suppose interactions between m genes are encoded by .…”
Section: Methodsmentioning
confidence: 99%
“…Another case study on breast cancer metastasis prediction also showed that several most popular pathway or network-based approaches [71-73] even cannot compete with a simple, single genes based classifier in an extensive and critical comparison [74]. In Figure 4, we showed an intuitional comparison of the results respectively produced by conventional network-based gene ranking (similar to PageRank algorithm used by Google) [76], 2D hierarchical clustering [77] and ACOR [67-69], for analyzing a BRCA-related protein interaction network [68]. From this comparison, we can see directly that only ACOR approach can reorder the adjacency matrix of the BRCA-related protein network to a meaningful pattern, which has many clusters closely overlapped.…”
Section: Network Analysis For Complex Protein Networkmentioning
confidence: 99%